1990
DOI: 10.1227/00006123-199006000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical versus Subclinical Pituitary Apoplexy: Presentation, Surgical Management, and Outcome in 21 Patients

Abstract: A retrospective review of 16 consecutive patients with pituitary apoplexy treated over a 10-year period is reported. Eight men and 8 women (mean age, 48 years) underwent transsphenoidal decompression after an average duration of symptoms of 19 days. The diagnosis of pituitary apoplexy was made by the sudden onset of headache (88%), nausea (56%), or meningismus (13%), with or without visual disturbances (75%), in the setting of a sellar tumor on computed tomographic or magnetic resonance imaging scans. Thirteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
145
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(154 citation statements)
references
References 0 publications
5
145
1
3
Order By: Relevance
“…1,7 In the present case, in retrospect, we should have suspected that the presence of an unusual flow-void protrusion suggested a vascular component from the ICA. If a pituitary adenoma is present, the possibility of a coincidental aneurysm should always be considered.…”
Section: Stroke February 2001mentioning
confidence: 63%
See 1 more Smart Citation
“…1,7 In the present case, in retrospect, we should have suspected that the presence of an unusual flow-void protrusion suggested a vascular component from the ICA. If a pituitary adenoma is present, the possibility of a coincidental aneurysm should always be considered.…”
Section: Stroke February 2001mentioning
confidence: 63%
“…1,2 However, the exact mechanism of pituitary apoplexy is not always clear. 1,2 Recently, Provenzale et al 3 reported a case in which pituitary apoplexy occurred probably secondary to internal carotid artery (ICA) dissection. We present a case of pituitary apoplexy caused by an unsuspected aneurysmal bleeding into a pituitary adenoma.…”
mentioning
confidence: 99%
“…Isto está em concordância com outras publicações, em que as hemorragias intra-adenomatosas em sua maioria são silenciosas 2,11 . Setenta e cinco por cento dos tumores hipofisários, em nossa casuística, eram não funcionantes.…”
Section: Discussionunclassified
“…Dos 3 pacientes com cefaléia 2 melhoraram após o procedimento cirúrgico. Esses resultados estão em concordância com os resultados de Onesti e col. 2 , em que 13 de 16 pacientes (81.2%) apresentaram melhora neurológica após tratamento neurocirúrgico. O grau de melhora visual parece relacionar-se mais ao grau de acometimento campimétrico pré-operatório e ao grau de palidez papilar, do que ao grau de acometimento visual isoladamente 2 , como ocorre nos casos de apoplexia aguda (observação pessoal).…”
Section: A B C Dunclassified
See 1 more Smart Citation